Lattice dynamics and phase transitions in Sn₂P₂S(Se)₆ ferroelectric crystals - Yevych, R.M.; Vysochanskii, Yu.M. (Condensed Matter Physics, 2006)
Polarizable ion model was used in describing the lattice dynamics in the Sn₂P₂S₆ and Sn₂P₂Se₆ ferroelectric crystals and their solid solutions. There has been obtained a good agreement of the calculated phonon spectra with the experimental data of Raman and Brillouin spectroscopies, neutron scattering and ultrasound experiments. Paraelectric phase instability has been modelled by negative charge transferring from the tin cations to the chalcogen ions, and by increasing the polarizabilities of the latter. The ferroelectric phase has been stabilized by tin atom displacement from centrosymmetric positions and a partial reversal recharging between tin and chalcogen ions. The effective charges decreasing by moving from Sn₂P₂S₆ to Sn₂P₂Se₆ compounds determine the shift of condensation wave vector of soft optic phonons in paraelectric phase from q = 0 in sulfur compound to q > 0 in selenium compound. Such a change of dynamical instability character is connected with the appearance of incommensurate phase in Sn₂P₂(SexS₁₋x)₆ solid solution under x > 0.28. The “two-mode” instability emerged as possible in the vicinity of Lifshitz point – there have been modelled the condensation of soft optic mode with q ≈ 0 and mixed optic and transversal acoustic phonons near q > 0. This fact requires further experimental and theoretical investigations Модель поляризованих iонiв застосована для опису динамiки ґратки сеґнетоелектричних кристалiв Sn₂P₂S₆ та Sn₂P₂Se₆, а також їх твердих розчинiв. Отримано добре узгодження розрахованих фононних спектрiв з даними спектроскопiї комбiнацiйного та мандельштам–брiллюенiвського розсiювання, ультразвукових дослiджень, розсiювання нейтронiв. Нестабiльнiсть параелектричної фази моделюється перенесенням негативного заряду з катiонiв олова на атоми халькогенiв, та збiльшенням поляризованостi останнiх. Сеґнетоелектрична фаза стабiлiзується зсувом атомiв олова з центросиметричних позицiй та частковою зворотною перезарядкою мiж iонами халькогену та олова. Зменшення iонних зарядiв при переходi вiд Sn₂P₂S₆ до Sn₂P₂Se₆ визначає зсув хвильового вектора конденсацiї м’яких оптичних фононiв параелектричної фази вiд q = 0 в сульфiднiй сполуцi до q > 0 в селенiднiй сполуцi. Така змiна характеру динамiчної нестабiльностi пов’язана з виникненням неспiвмiрної фази в твердих розчинах Sn₂P₂(SexS₁₋x)₆ при x > 0.28. Виявлена можливiсть “двомодової” нестабiльностi в околi точки Лiфшиця — тут моделюється конденсацiя м’якої оптичної моди при q ≈ 0 та змiшаних оптичних та поперечних акустичних фононiв при q > 0, що потребує подальших експериментальних i теоретичних дослiджень.